2000
DOI: 10.1006/exnr.1999.7335
|View full text |Cite
|
Sign up to set email alerts
|

Metallothioneins Are Upregulated in Symptomatic Mice with Astrocyte-Targeted Expression of Tumor Necrosis Factor-α

Abstract: Transgenic mice expressing TNF-␣ under the regulatory control of the GFAP gene promoter (GFAP-TNF␣ mice) exhibit a unique, late-onset chronic-progressive neurological disorder with meningoencephalomyelitis, neurodegeneration, and demyelination with paralysis. Here we show that the metallothionein-I ؉ II (MT-I ؉ II) isoforms were dramatically upregulated in the brain of symptomatic but not presymptomatic GFAP-TNF␣ mice despite TNF-␣ expression being present in both cases. In situ hybridization analysis for MT-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…During CNS inflammation, major MT‐I + II regulatory factors are proinflammatory cytokines and especially interleukin (IL)‐6 [1]. Accordingly, IL‐6, IL‐3, tumor necrosis factor (TNF)‐α, macrophage‐colony stimulating factor (M‐CSF), and interferons increase brain MT‐I + II expression in a cytokine‐specific manner as demonstrated by using transgenic mice with cytokine overexpression [48–51] or cytokine deficiency [29,52–55].…”
Section: Regulation Of Mt‐i + IImentioning
confidence: 99%
“…During CNS inflammation, major MT‐I + II regulatory factors are proinflammatory cytokines and especially interleukin (IL)‐6 [1]. Accordingly, IL‐6, IL‐3, tumor necrosis factor (TNF)‐α, macrophage‐colony stimulating factor (M‐CSF), and interferons increase brain MT‐I + II expression in a cytokine‐specific manner as demonstrated by using transgenic mice with cytokine overexpression [48–51] or cytokine deficiency [29,52–55].…”
Section: Regulation Of Mt‐i + IImentioning
confidence: 99%
“…Studies of in situ hybridization (21, 24-28) and immunohistochemistry (19,21,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), have demonstrated that MT-1&2 expression occurs throughout the brain and spinal cord, and that the principal cellular source is the astrocyte, particularly following injury. Significant MT-1&2 expression is also found in ependymal cells, epithelial cells of the choroid plexus, meningeal cells of the pia mater and endothelial cells of blood vessels, while neurons appear to express very low levels.…”
Section: Metallothionein-1and2 Are Preferentially Expressed In Reactivementioning
confidence: 99%
“…Although in most cases no thorough cell identification has been established by robust methods such as double labeling or use of the MT-3 KO mice as controls, in the normal brain it appears that the MT-3 mRNA signal is more consistent with neuronal than with glial cells, with astrocyte MT-3 upregulation eventually occurring following injury (26,27,36,53,(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68). In contrast to the MT-3 messenger, the MT-3 protein has been shown to be present mainly in astrocytes by a number of studies (36,40,65,66,(69)(70)(71)(72)(73)(74). Other reports, however, show MT-3 protein presence basically in neurons (63,64,(75)(76)(77).…”
Section: Expression Of Metallothionein-3 In the Central Nervous Systemmentioning
confidence: 99%
“…Several CNS pathologies involve inflammatory mediators, including stroke, brain trauma, seizures, ischemia (Olanow, 1993;Yankner, 1996;Price et al, 1998;Penkowa et al, 1999Penkowa et al, , 2000aCarrasco et al, 2000), and neurodegenerative disorders such as Alzheimer's and Parkinson's diseases (for review see Campbell, 1998;Culpan et al, 2003;Ethell and Buhler, 2003;McGeer and McGeer, 2003;Eissner et al, 2004). Inflammation may be a protective mechanism that isolates the injured area, destroys affected cells, and repairs the extracellular matrix; however, chronic presence of inflammatory mediators may be followed by increased oxidative stress and cell death (for review see Muñoz-Fernandez and Fresno, 1998;Hicks et al, 1999;Shohami et al, 1999;Sayer et al, 2002;Rothwell, 2003).…”
mentioning
confidence: 98%